PEMBERIAN SANKSI PIDANA POKOK BERUPA PENJARA DAN LATIHAN KERJA DALAM TINDAK PIDANA PENGANIAYAAN BERAT OLEH ANAK: The Imposition Of Primary Criminal Sanctions In The Form Of Imprisonment And Work Training In Cases Of Severe Physical Assault By Juveniles - Arulia Corin Hamida; Vience Ratna Multiwijaya (AMICUS CURIAE, 2025)
The imposition of criminal sanctions by the judge on juvenile perpetrators of severe physical assault involves two primary criminal sanctions, namely imprisonment and work training. The core issue raised is whether the imposition of primary criminal sanctions by the judge, in the form of imprisonment and work training, aligns with Law Number 11 of 2012 concerning the Juvenile Justice System. The methodology employed consists of using court decisions as the research object, conducting normative research or literature review, employing a descriptive-analytical research nature, utilizing secondary data sourced from literature studies and interviews with informants, analyzing the data through qualitative analysis methods, and drawing conclusions through deductive logic. The author concludes that the imposition of criminal sanctions in the form of imprisonment and work training on juvenile defendants of severe physical assault is not in accordance with Law Number 11 of 2012 concerning the Juvenile Justice System. The research findings suggest that the imposition of sanctions by the judge in cases of severe physical assault by juveniles should consider the recommendations of social workers, namely imposing work training as the primary criminal sanction for the juveniles.